2010
DOI: 10.1080/12265934.2010.9693672
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Bus Rapid Transit on Location Choice of Creative Industries and Employment Density in Seoul, Korea

Abstract: Bus rapid transit (BRT) has been a promising form of public transportation due to a higher burden of rail transit construction and operation. Many urban economists and planners argue that convenient public transit is one of the core urban strategies to attract and retain creative industries and increase employment density. Although many leaders of cities in the world pay attention to the new type of public transit, we have less understanding of the BRT impact on the location choice of creative industries and j… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 16 publications
(7 reference statements)
1
10
0
Order By: Relevance
“…Vincent and Callaghan (2008) also examined TOD projects in York Region, Ontario, and El Monte, California, and Downloaded by [University of Western Ontario] at 09:14 12 April 2015 concluded that the type and level of investment occurring near BRT stations was comparable to that of TOD near the rail transit. Kang (2010) confirmed that BRT is associated with the location of creative industries and service sectors within 500 m of bus stops in Seoul, Korea. The BRT operation was shown to increase the employment density in the vicinity of stations by up to 54%.…”
Section: Change In Densities Land Use and Location Decisionssupporting
confidence: 83%
“…Vincent and Callaghan (2008) also examined TOD projects in York Region, Ontario, and El Monte, California, and Downloaded by [University of Western Ontario] at 09:14 12 April 2015 concluded that the type and level of investment occurring near BRT stations was comparable to that of TOD near the rail transit. Kang (2010) confirmed that BRT is associated with the location of creative industries and service sectors within 500 m of bus stops in Seoul, Korea. The BRT operation was shown to increase the employment density in the vicinity of stations by up to 54%.…”
Section: Change In Densities Land Use and Location Decisionssupporting
confidence: 83%
“…While, as described, existing studies show a relationship between economic development and BRT, we currently have a limited understanding of how BRT impacts the location choice of specific industries (Graham, 2007;Kang, 2010). Other studies that intersect transit and economic development often focus on rail transit (Bollinger and Ihlanfeldt, 1997;Graham, 2007;Nelson et al, 2013;Polzin, 1999).…”
Section: Brt and Economic Developmentmentioning
confidence: 99%
“…Such physical features provide community members and developers with a sense of permanence, which the fixed-rail investment of an LRT typically signifies (Cervero and Dai, 2014;Davis et al, 2007;Polzin and Baltes, 2002;Polzin, 1999). BRT systems are easier to construct with gradual investment to include different routes and operational features (Cervero and Dai, 2014;Hook et al, 2013;Kang, 2010;Polzin and Baltes, 2002). Through case studies of six cities (Pittsburgh, Los Angeles, New York, etc.…”
Section: Background: What Is Brt and How Does It Compare To Lrt?mentioning
confidence: 99%
See 2 more Smart Citations